1997
DOI: 10.1143/jjap.36.4928
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Thin Films and Nanosize Powders by Intense, Pulsed Ion Beam Evaporation

Abstract: Efficient preparation of thin films has been achieved with a high-density ablation plasma produced by the interaction of an intense, pulsed ion beam with solid targets, a process called ion beam evaporation, having an instantaneous deposition rate of cm/s. In addition to standard front-side deposition, backside deposition, in which the substrate is placed on the reverse side of the holder, has been proposed to produce good quality thin films, though the deposition rate is one order of magnitude less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Regarding the charging voltage of the pulse-forming line, resonant charging occurs at around t = 210 ns. Experiments with magnetically insulated ion diodes using the gas-puff nitrogen ion source [13] showed that the ion beams included pro- tons in addition to monovalent and bivalent nitrogen. Dependence of the peak ion current density (J i ) on the delay time (τ PM ) is presented in Fig.…”
Section: Ion Acceleration Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the charging voltage of the pulse-forming line, resonant charging occurs at around t = 210 ns. Experiments with magnetically insulated ion diodes using the gas-puff nitrogen ion source [13] showed that the ion beams included pro- tons in addition to monovalent and bivalent nitrogen. Dependence of the peak ion current density (J i ) on the delay time (τ PM ) is presented in Fig.…”
Section: Ion Acceleration Experimentsmentioning
confidence: 99%
“…In this work, we define as intense beams with pulse width of 50 to 1000 ns and ion current above 1 kA. Therefore, the pulsed ion beams have been studied for applications in material processings, such as surface treatment of metals, ceramics, and other materials [8][9][10], thin-film deposition [11,12], preparation of ultrafine particles [10,13], ion implantation [14], annealing [15], and other fields of material science. In 1990s, it was found that irradiation of pulsed ion beam on materials achieves adiabatic heating of surface layers at the depth of ion penetration (several hundreds of nanometers) and rapid quenching through thermal diffusion into bulk after irradiation, which is distinguished from the conventional ion beam irradiation technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] 1) Due to the use of a high-density plasma, the deposition rate is very high. 2) Because the ablation plasma carries a large amount of thermal energy, it deposits this energy together with the thin film, resulting in an instantaneous high temperature on the surface of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…1988 by using high density ablation plasma produced by the pulsed ion beam interaction with solid targets, called pulsed ion beam evaporation (BE) [1]- [4]. Quick preparation has been available w i t h good stoichiometry, without heating the substrate.…”
Section: Expeiumetal Setupmentioning
confidence: 99%